Experimental infection of wild boars (Sus scrofa) with Rickettsia rickettsii and evaluation of the transmission potential to Amblyomma sculptum ticks - Lucianne Cardoso Neves; Lina de Campos Binder; Warley Vieira de Freitas Paula; Nicolas Jalowitzki de Lima; Ennya Rafaella Neves Cardoso; Rayane Almeida Santos; Raphaela Bueno Mendes Bittencourt; Gracielle Teles Pádua; Gabriel Cândido dos Santos; Mariana Avelar Tavares; Maria Carolina de Azevedo Serpa; Adriano Pinter; et al. (Parasites & Vectors)
Abstract Background Brazilian spotted fever is a tick-borne disease caused by the bacterium Rickettsia rickettsii, whose main vector in Brazil is the tick Amblyomma sculptum. Amplifying hosts are essential for the perpetuation of this bacterium in the tick population as they can be sources of infection during bacteremic periods. Recent studies demonstrated the ability of suids (Sus scrofa) to sustain populations of A. sculptum, one of the main tick species found parasitizing wild boars in the midwestern and southeastern regions of Brazil. In this study, wild boars were experimentally infected with R. rickettsii by tick infestation and were evaluated for their ability to transmit the infection to A. sculptum ticks, under laboratory conditions. Methods Four wild boars were infected with R. rickettsii through infestation with R. rickettsii-infected A. sculptum adults (infected group); a fifth wild boar was infested with uninfected A. sculptum adults (control group). Simultaneously, the animals were infested with uninfected larvae and nymphs of A. sculptum. The wild boars were monitored for 28 days by clinical examination and hematological tests, real-time quantitative PCR (qPCR) of blood for the detection of Rickettsia and inoculation of blood in guinea pigs. IgG antibody titers were followed until the end of the experiment. Unfed nymphs and adults, molted from engorged larvae and nymphs that fed on wild boars, were used to infest susceptible guinea pigs and rabbits; some of these unfed ticks were tested by qPCR for rickettsial detection. Results The wild boars showed no clinical or hematological alterations, and bacteremia was not detected by qPCR or inoculation of wild boar blood into guinea pigs. Furthermore, wild boars showed a moderate humoral response, with anti-R. rickettsii endpoint titers up to 256 or 512. Rickettsial DNA was not detected in molted ticks after acquisition feeding on wild boars. Moreover, no disease or seroconversion was observed in guinea pigs and rabbits that were infested with ticks originated from wild boar acquisition feeding. Conclusions Wild boars seroconverted to Rickettsia spp. after being infested with R. rickettsii-infected A. sculptum; however, they did not develop bacteremia and did not act as competent amplifying hosts of R. rickettsii for A. sculptum ticks. Graphical Abstract